Kemampuan Level Representasi Kimia Murid Kelas X pada Materi Hukum-Hukum Dasar Kimia - Gilang Fadjar Azani; Abdullah Abdullah; Erviyenni Erviyenni (Lembaga Yasin AlSys, 2026)
The ability to use chemical representation levels is important in helping students understand chemistry concepts comprehensively through the interconnection of macroscopic, microscopic, and symbolic representations. The Basic Laws of Chemistry is a fundamental topic that requires students to be able to connect these three levels of representation; however, students still experience difficulties, especially in understanding concepts at the particle or microscopic level. This study aims to describe the chemical representation level ability of Grade X students on the topic of the Basic Laws of Chemistry at SMA Negeri 9 Pekanbaru. This study used a quantitative descriptive approach with a survey design. The research sample consisted of 102 students from classes X-5, X-6, and X-7, selected using cluster sampling. Data were collected using a written essay test consisting of 15 items and covering three levels of chemical representation, namely macroscopic, microscopic, and symbolic. The data were analyzed descriptively and quantitatively by calculating the percentage of students’ ability at each level of representation. The results showed that students’ overall chemical representation level ability was in the good category, with an average percentage of 75%. Symbolic representation ability obtained the highest percentage, at 78%, in the good category, followed by macroscopic representation at 76% in the good category and microscopic representation at 70% in the good category. These findings indicate that students more easily understand chemistry concepts in the form of symbols and calculations than abstract concepts at the particle level. The conclusion of this study emphasizes that students’ microscopic representation ability still needs to be improved so that the interconnection among macroscopic, microscopic, and symbolic representations can be formed more optimally in chemistry learning.